Inflammation-activated C/EBPβ mediates high-fat diet-induced depression-like behaviors in mice - Li, Yiyi; Chen, Hongyu; Wang, Jianhao; Wang, Jiabei; Niu, Xuan; Wang, Chao; Qin, Dongdong; Li, Fang; Wang, Yamei; Xiong, Jing; Liu, Songyan; Huang, Liqin; et al. (Frontiers in Molecular Neuroscience, 2022)
Depression, one of the most common causes of disability, has a high prevalence rate in patients with metabolic syndrome. Type 2 diabetes patients are at an increased risk for depression. However, the molecular mechanism coupling diabetes to depressive disorder remains largely unknown. Here we found that the neuroinflammation, associated with high-fat diet (HFD)-induced diabetes and obesity, activated the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) in hippocampal neurons. This factor repressed brain-derived neurotrophic factor (BDNF) expression and caused depression-like behaviors in male mice. Besides, the loss of C/EBPβ expression in C/EBPβ heterozygous knockout male mice attenuated HFD-induced depression-like behaviors, whereas Thy1-C/EBPβ transgenic male mice (overexpressing C/EBPβ) showed depressive behaviors after a short-term HFD. Furthermore, HFD impaired synaptic plasticity and decreased surface expression of glutamate receptors in the hippocampus of wild-type (WT) mice, but not in C/EBPβ heterozygous knockout mice. Remarkably, the anti-inflammatory drug aspirin strongly alleviated HFD-elicited depression-like behaviors in neuronal C/EBPβ transgenic mice. Finally, the genetic delivery of BDNF or the pharmacological activation of the BDNF/TrkB signaling pathway by 7,8-dihydroxyflavone reversed anhedonia in a series of behavioral tests on HFD-fed C/EBPβ transgenic mice. Therefore, our findings aim to demonstrate that the inflammation-activated neuronal C/EBPβ promotes HFD-induced depression by diminishing BDNF expression.